Impact of Parkinson's disease on perioperative complications and hospital cost in multilevel spine fusion: A population-based analysis. (January 2017) - McClelland, Shearwood; Baker, Joseph F.; Smith, Justin S.; Line, Breton G.; Errico, Thomas J.; Ames, Christopher P.; Bess, R. Shay
Highlights: A 12-year nationwide analysis indicates that PD is significantly associated with increased in-hospital morbidity, mortality, and cost following spine fusion of 1–2 levels when compared with the general population. These findings point to the need for risk stratification and adjustment of quality metrics for this growing patient population. Abstract: Parkinson's disease (PD) is a neurodegenerative disorder manifesting over time to result in reduced mobility. The impact of PD on spinal fusion has yet to be addressed on a nationwide level. The Nationwide Inpatient Sample (NIS) from 2001 to 2012 was used for analysis. Admissions with spinal fusion of two or more vertebrae (ICD-9 codes = 81.62, 81.63 and 81.64) were included and then stratified based on the presence or absence of PD (ICD-9 code = 332.0); patients with cancer (ICD-9 codes = 140–239) or trauma (ICD-9 codes = 805.0–806.9) were excluded. Propensity score matching adjusted for potential confounding effects introduced by patient age, race, sex, and primary payer for care. 570, 858 patients receiving spinal fusion of two or three vertebrae (1–2 levels) were identified, 2648 (0.5%) of whom had PD. Analysis revealed that PD was independently predictive for increased in-hospital mortality, durotomy, paraplegia, postoperative infection, venous thrombotic events, inferior vena cava filter placement, red blood cell transfusion, pulmonary embolism, total hospital charge >$200, 000, length of stay >1 week, non-routine discharge disposition, acute respiratory distress syndrome, acute posthemorrhagic anemia, multisystem complications (nervous system, cardiac, respiratory, urinary), and device-related complications (all P  < 0.001). In conclusion, these findings from a nationwide analysis comprising a 12-year period indicate that PD is significantly associated with increased in-hospital morbidity, mortality, and cost following spine fusion of 1–2 levels when compared with the general population. These findings point to the need for risk stratification and adjustment of quality metrics for this growing patient population, and should be integrated into operative decision-making and patient counseling.